A Spiky Silver‐Iron Oxide Nanoparticle for Highly Efficient Targeted Photothermal Therapy and Multimodal Imaging of Thrombosis (Small 11/2023). Issue 11 (15th March 2023) - Vazquez‐Prada, Karla X.; Moonshi, Shehzahdi S.; Wu, Yuao; Akther, Fahima; Tse, Brian W.C.; Sokolowski, Kamil A.; Peter, Karlheinz; Wang, Xiaowei; Xu, Gordon; Ta, Hang Thu
Abstract : Theranostics of Thrombosis In article number 2205744, Hang Thu Ta and co‐workers present a novel nanoparticle (AgIONP) for theranostics of thrombosis. AgIONPs can specifically bind to thrombus. Exposure of AgIONPs to a near‐infrared laser leads to thrombolysis and restoration of the blood flow. AgIONPs can also be used as a multimodal diagnostic agent.